Methods—A Practical Approach to the Reversible Hydrogen Electrode Scale. Issue 6 (1st June 2022) - Zamora Zeledón, José A.; Jackson, Ariel; Stevens, Michaela Burke; Kamat, Gaurav A.; Jaramillo, Thomas F.
Abstract : Accurately quantifying applied potential is important to ensuring the comparability, accuracy, and precision of electrochemical studies. Reference electrodes (REs) enable knowledge/determination of the applied potential at electrodes in electrochemical systems. Ultimately, the choice of RE will depend on the particular requirements of a given electrochemical system, however, we note it is imperative to ensure the accuracy of the RE potential and its proper translation to a standardized scale. In this work, we highlight that while there are many commercially available REs, these must be experimentally calibrated to a reliable and practical standard potential scale, for instance the reversible hydrogen electrode (RHE) scale for aqueous systems. With representative data, we provide streamlined instructions on how to calibrate any RE to the RHE scale. We also provide guidance to mitigate and/or avoid possible electrolyte contamination issues arising from REs. Moreover, we offer a step-by-step guide on how to build a practical RHE RE, which may be a suitable and desirable option in certain applications. Our work emphasizes the need for the continuous adoption of standardized reference potential scales and demonstrates the versatility of the RHE scale, particularly in aqueous electrochemistry.